A representação social do kanaimî, do piya'san e do tarenpokon nas Malocas Canta Galo e Maturuca - Rabelo Filho, Manoel Gomes (2012)
Our study aims to understand the social representations of Kanaimî, the shaman and the people Tarenpokon Macuxi, in Canta's Galo and Maturuca's Villages, located in northeastern Roraima. Aimed to deepen the ideas that the Indians of these places have these characters on the culture in order to make their meaning and relate them to the religion. The initial research was literature in order to observe how the Kanaimî understood, and the shaman Tarenpokon in the past. We conduct interviews, which were used to support the verification of representations today, and analysis with reference to the theory of social representation. The Kanaimî, spiritual and starring as a character constant violent attacks, manifests and promotes terror to Indians. This causes the Indians to perform a series of rituals in order to keep them away from their paths. The shaman, as a trustee for many health and spiritual problems of the indigenous Macuxi, media to solve these problems together with the spiritual beings as possible. The Tarenpokon also as a healer capable of providing health, conducts prayer sessions that acts on the various "bichos" (bugs) to keep them or convince them to heal people. We relate these explanations to the cosmovision of the Macuxi to understand its religious manifestations. We have based historical studies and socio-anthropological aspects of the existing religious Macuxi that relate to the characters - Kanaimî, shaman and Tarenpokon - expanding their social representations and specifying the meanings they have